PERMINTAAN DAN PENDAPATAN PEDAGANG BUAH JPERMINTAAN DAN PENDAPATAN PEDAGANG BUAH JERUK BRASTAGI DI TINGKAT PENGECER DI KOTA BENGKULUERUK BRASTAGI DI TINGKAT PENGECER DI KOTA BENGKULU - Utama, Satria Putra; Sugiarti, Sri; Purba, Bosko (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2005)
Retailer demand on Brastagi orange is derivate from consumers demand or people in Bengkulu city. On the other hand, there were some factors that influenced demand of Brastagi orange on retailers themselves beside influencing by factor from consumer, like: the number of Brastagi orange that ordered or bought by retailer in the last month, the price of Brastagi orange bought in this month, the price of Brastagi orange in the retailer in this month, the price of Brastagi orange on the retailer in the last month, the price of Bengkulu (local) orange in the retailer, the number of Brastagi orange that ordered or bought by consumers in the last month, capital and dummy of place for retailers. Descriptive analysis was shows that the biggest number of month ordered of Brastagi orange is the demand of Brastagi Orange on AB type in awning retailer, on the other side the biggest demand for Brastagi orange from the retailer without awning is on super type with the source of the whole buying from the agent in Bengkulu City. The system of payment from the agent is pay after sale. The result of data analysis and hypothesis test (t test) shows that the price of retailer Brastagi Orange order in this month (X1), capital (X3), the number of Brastagi orange that bought in the last month (x4t-1), and dummy of trade location (D) were influenced or significant as partial on Brastagi orange retailer demand . On the other side, the price of Bengkulu Local orange (X2) was not influence on retailer demand on retailer Brastagi orange. The result of the income analysis were shows that the amount of income from Brastagi orange retailer with awning per month and the income of the Brastagi orange retailer without awning month. However, the result of analysis from statistic test shows that different of income retailer with awning compare to retailer without awning was not significant.